Kepemimpinan Kepala Sekolah dalam Pengembangan Lembaga Pendidikan Islam Sekolah Kreatif SD Muhammadiyah Kota Madiun - Suwardi Suwardi; Samino Samino (Manajemen Pendidikan, 2014)
This study aims to reveal the type of school leadership, creative efforts in developing creative educational institutions and Superior, with a sub-focus include : (1) What type of leadership that principals applied in the development of Islamic education institutions Creative Muhtadin elementary school (2) any efforts made  in the development of the principal institutions of Islamic Education Creative Muhtadin elementary school and (3) the desired output targets Creative Muhtadin elementary school. This study uses qualitative research in the form of case studies. The data was collected by interview, observation, and documentation. While the techniques of data analysis, researchers use interactive model containing four interrelated components, namely: collection of data, simplification of data, exposure data, and drawing conclusions and filing. The results showed that : (1) the type of principal who applied leadership creative elementary school Muhtadin, the democratic leadership (aspirational accommodating, assertif and open), where the principal during the leadership is able to make changes and have a vision for the future of Islamic education institutions to develop Creative Muhtadin elementary school towards creative and superior schools; (2) any efforts made    in the development of the principal institutions of Islamic Education Creative Muhtadin elementary school build a school system; (3) how the desired output targets elementary school creative Muhtadin, namely : initial output (Preliminary Results) and general output targets include.